2017
DOI: 10.5468/ogs.2017.60.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative administration of propranolol to women undergoing ovarian cancer surgery: A pilot study

Abstract: ObjectiveThis study was done to evaluate whether perioperative propranolol (ß-blocker) in ovarian cancer patients undergoing debulking surgery reduced perioperative tumor growth induced by surgical stress.MethodsThis was a prospective randomized single institution analysis. The primary objective was to compare the changes in CA 125 level (changes between preoperation day 2 and postoperative day 7). As a study arm, patients received a low dose of propranolol 40 mg/day (4×10 mg) starting two days before surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 27 publications
1
32
0
1
Order By: Relevance
“…Previous retrospective cohort studies have also suggested that using beta blockers in EOC patients is associated with longer survival [14,15,23]. A pilot study demonstrated the potential role of perioperative propranolol to suppress tumor growth in EOC patients [24]. However, there are several studies with no improved survival in BB users [16,25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous retrospective cohort studies have also suggested that using beta blockers in EOC patients is associated with longer survival [14,15,23]. A pilot study demonstrated the potential role of perioperative propranolol to suppress tumor growth in EOC patients [24]. However, there are several studies with no improved survival in BB users [16,25].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, although β-blockade and semiselective COX2 inhibition showed beneficial effects separately, their combined use was superior and, in some models, was the only effective approach; this was evident when the β-blocker propranolol was combined with the semiselective COX2 synthesisinhibitor etodolac. 12,22,33,66,67,84,89 Retrospective clinical studies have provided inconclusive results regarding incidental perioperative or chronic use of β-blockers, with several studies, [90][91][92] but not others, 93,94 reporting beneficial effects on long-term cancer outcomes, especially with respect to nonselective β-blockade. Perioperative COX inhibition also has provided inconclusive results, as recently reviewed by Cata et al 43 Notably, aspirin, a nonselective COX inhibitor, was recently recommended for the prevention of colorectal cancer (CRC) in men at risk between the ages of 50 and 59 years.…”
Section: Inhibition Of Perioperative Sirs and Its Effects On Metastasismentioning
confidence: 99%
“…Помимо химиотерапии, предпринимаются попытки применения препарата в хирургической практике. В частности, в пилотном исследовании периоперационное введение пропранолола снижало уровень СА-125 в сыворотке крови после операции в сравнении с пациентами, не получавшими препарат [43]. Несмотря на то, что данный проект является пилотным, полученные результаты могут стать толчком в дальнейшем исследовании пропранолола в хирургической практике.…”
Section: методы перепрофилированияunclassified